2010
DOI: 10.1002/art.27623
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a cohort of Danish patients with fibromyalgia: Increased frequency of suicide

Abstract: Objective. A previous study demonstrated an association between self-reported widespread body pain and increased mortality. The aim of this study was to analyze whether fibromyalgia (FM) and FM-like symptoms are related to increased mortality.Methods. From hospital records, we identified 1,361 patients referred during the period 1984-1999 because of the suspicion of FM. The cases were reviewed by reviewers who were blinded to the outcome. The cohort was followed up for a total of 5,295 person-years at risk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 44 publications
1
84
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7] The conflicting results may be attributable to differences in the populations studied and in the definitions used to identify chronic pain. Most importantly, possible mechanisms underlying the association between fibromyalgia and increased mortality, if any, should be explored.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The conflicting results may be attributable to differences in the populations studied and in the definitions used to identify chronic pain. Most importantly, possible mechanisms underlying the association between fibromyalgia and increased mortality, if any, should be explored.…”
mentioning
confidence: 99%
“…1,2 Several longitudinal epidemiologic investigations have demonstrated significant positive associations between pain conditions and completed suicides. [3][4][5][6] Case control studies of premorbid pain among suicide victims 7,8 and prospective case series studies of pain clinic or rheumatology patients [9][10][11] have also indicated that those with CP have an increased risk of completed suicide.…”
mentioning
confidence: 99%
“…50 In a Danish study fibromyalgia patients had suicide rate of 10.5 times that of the general population. 51 Apart from caution in the use of SSRIs, the management of psychiatric disorders in fibromyalgia patients follows the usual guidelines for nonfibromyalgia patients.…”
Section: Psychiatric Disordersmentioning
confidence: 99%